Thermal performance of the horizontal opening in the traditional houses of old Biskra. Case of traditional house at Bab Edarb - Alkama, Djamel; Madhoui-Benchikha, Meriem (Journal of Applied Engineering Science & Technology, 2018)
This research aims to revive a traditional architecture heritage of Biskra, which is the horizontal opening in the roof of the "wast edar" named “raouzna". In order to evaluate the thermal performance of this element and measure its ability to control the distribution of interior temperature in a region submitted to a hot and dry climate, an experimental study by numerical simulation was carried out. DEROB-LTH program was used to perform the work of simulation which focused on one set of constant and variable factors. These factors are related to climate data, thermal’s comfort zone and to the dimensions and shape of the raouzna. Some of the data used for the simulation are based on the results of a typo-morphological analysis of a corpus of traditional houses and a survey carried out upstream in the quarter of Bab Edarb (old Biskra). The study focuses on the comparison between the recorded temperature inside the traditional house and the outside air, and for periods critical of winter and summer represented respectively by the coldest month and hottest: January and July.